THE PHOTOCHEMICAL NATURE OF THE PHOTOSENSORY PROCESS - Hecht, Selig (The Rockefeller University Press, 1920)
On page 243, Vol. ii, No. 3, January 20, 1920, line 12 (counting each equation as a line) for a photochemical reaction read a reversible photochemical reaction.